Loss of functional OPA1 unbalances redox state: implications in dominant optic atrophy pathogenesis. Issue 6 (25th April 2016) - Millet, Aurélie M. C.; Bertholet, Ambre M.; Daloyau, Marlène; Reynier, Pascal; Galinier, Anne; Devin, Anne; Wissinguer, Bernd; Belenguer, Pascale; Davezac, Noélie
Abstract: Objective: OPA1 mutations cause protein haploinsufficiency leading to dominant optic atrophy (DOA), an incurable retinopathy with variable severity. Up to 20% of patients also develop extraocular neurological complications. The mechanisms that cause this optic atrophy or its syndromic forms are still unknown. After identifying oxidative stress in a mouse model of the pathology, we sought to determine the consequences of OPA1 dysfunction on redox homeostasis. Methods: Mitochondrial respiration, reactive oxygen species levels, antioxidant defenses, and cell death were characterized by biochemical and in situ approaches in both in vitro and in vivo models of OPA1 haploinsufficiency. Results: A decrease in aconitase activity suggesting an increase in reactive oxygene species and an induction of antioxidant defenses was observed in cortices of a murine model as well as in OPA1 downregulated cortical neurons. This increase is associated with a decline in mitochondrial respiration in vitro. Upon exogenous oxidative stress, OPA1‐depleted neurons did not further exhibit upregulated antioxidant defenses but were more sensitive to cell death. Finally, low levels of antioxidant enzymes were found in fibroblasts from patients supporting their role as modifier factors. Interpretation: Our study suggests that the pro‐oxidative state induced by OPA1 loss may contribute to DOA pathogenesis and that differences in antioxidant defenses can explain the variability in expressivity. Furthermore, antioxidants may be used as therapy as they could prevent or delay DOA symptoms in patients.